2012
DOI: 10.1016/j.vaccine.2011.10.098
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with NS1-truncated H3N2 swine influenza virus primes T cells and confers cross-protection against an H1N1 heterosubtypic challenge in pigs

Abstract: The diversity of contemporary swine influenza virus (SIV) strains impedes effective immunization of swine herds. Mucosally delivered, attenuated virus vaccines are one approach with potential to provide broad crossprotection. Reverse genetics-derived H3N2 SIV virus with truncated NS1 (NS1Δ126 TX98) is attenuated and immunogenic when delivered intranasally in young pigs. We analyzed T-cell priming and cross-protective efficacy in weanling piglets after intranasal inoculation with NS1Δ126 TX98 versus wild type T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 41 publications
(45 reference statements)
2
56
2
Order By: Relevance
“…Cross-reactive T cells primed by the WIV may also have contributed to the protective effect against the heterologous CO99 infection. Consistent with this possibility, a similarly formulated H1N2 WIV vaccine was shown to prime T cells in antibody-negative young pigs (7).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Cross-reactive T cells primed by the WIV may also have contributed to the protective effect against the heterologous CO99 infection. Consistent with this possibility, a similarly formulated H1N2 WIV vaccine was shown to prime T cells in antibody-negative young pigs (7).…”
Section: Discussionmentioning
confidence: 72%
“…This virus (identical to the LAIV in the present report) was shown to have attenuated replication in the upper respiratory tract. When the TX98 LAIV was administered as an intranasal vaccine to young seronegative pigs, it elicited a mucosal IgA response, modest titers of serum HI antibodies, and antigen-specific T cells, while conferring protection against homologous challenge and a degree of cross-protection against variant strains, with a single-or two-dose regimen (7,26). Our previous work indicated that two intranasal applications of the LAIV vaccine did not confer any benefit against homologous challenge compared to one dose (26), and one dose would be highly preferred for use in the swine population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While live attenuated influenza virus (LAIV) vaccines have been approved for use in people and horses, a LAIV for swine has yet to make it to market. This is despite a number of LAIV vaccines that have been developed and demonstrated to provide significant cross-protection in experimentally infected pigs (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In addition, these vaccines primarily generate antibody responses with limited or no cell-mediated immunity (CMI). In contrast, live attenuated influenza vaccines (LAIV) provide strong, long-lived cell-mediated and humoral immunity against different influenza virus subtypes with no need for perfect antigen matching (8)(9)(10)(11). Previously, it was shown that SIVs generated by genetic modifications within the hemagglutinin (HA) or nonstructural (NS) genes are attenuated in pigs (12,13).…”
mentioning
confidence: 99%